UPAYA PENINGKATAN PARTISIPASI SISWA DALAM PERMAINAN BOLA BAKAR MELALUI MODIFIKASI ALAT PEMUKUL PADA KELAS VI SD NEGERI 02 GERDU KECAMATAN KARANGPANDAN KABUPATEN KARANGANYAR TAHUN AJARAN 2012/2013 - NOVIYANTO, FAJAR (Jurnal Phederal Penjas, 2013)
The purpose of this study is to promote student participation in the game of fuelthrough the modification of a battering in the sixth grade elementary school District 02Gerdu Karangpandan Karanganyar Academic Year 2012/2013.This research is a classroom action research (CAR). The experiment wasconducted in two cycles. Subjects were students of class VI Elementary School 02 Gerdutotaling 30 children. Data sources are from teachers and students. Data collectiontechniques are obtained by observing during the learning process takes place. Thevalidity of data using triangulation techniques methods. Data analysis using descriptivequalitative. Research procedures are interrelated models.The results showed that through modification bat can increase studentparticipation in the game of fuel. Student participation in the learning process prasiklusstill low at 46.66%. The increase occurred in the first cycle is 73.33%. Implementationof the second cycle has increased student participation is higher, namely 83.33%. sothat it can support a quality learningConclusions: This study is a modification of a battering increase studentparticipation in the game of slagball in the sixth grade fuel Elementary School District02 Gerdu Karangpandan Karanganyar Academic Year 2012/2013.Keywords: student participation, slagball, modification bat